Instrument analysis of the effect of project-based learning models on learning outcomes on the basic competencies of commercial hair trimming - Sora, Maja Mustika; Maspiyah, Maspiyah; Hidayati, Lutfiyah (Universitas Malikussaleh, 2021)
This study was used to determine the feasibility of the instruments before being used for further research. This study calculates the results of the validation of three validators who are experts in their fields using arithmetic averages, the validated instruments are: (1) the syllabus gets a score of 92.67%; (2) Learning Implementation Plan (RPP) scored 94.4%; (3) The Knowledge Assessment Instrument received a score of 93.36%; (4) The skill assessment instrument got a score of 93.31%; (5) The attitude assessment instrument got a score of 96.89%; (6) The Project Based Learning module received a score of 93.1%. In addition, this study also calculates the validity of the items, the differentiability of the items, the level of difficulty of the items and the reliability test of the items. This question consists of 30 items that have been tested on 15 students to find out the results of the calculation: (7) the validity of the items obtained a significance level value (ɑ) 0.05; (8) the level of difficulty of the items obtained a percentage of 16.67 for the easy question category, 70% for the medium question category, and 13.33% for the difficult question category; (9) The differentiating power of the items has very good criteria; and (10) the reliability of the items got a score of 0.753. From the calculation results that have been mentioned, it can be stated that the instrument of the influence of project-based learning models on learning outcomes on the basic competencies of commercial hair trimming is declared feasible and can be used for further research.